Etika Komunikasi Politik dalam Perspektif Islam - Zikrullah; Mena Sari (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
This article aims to discuss Islamic views on political communication ethics. Through literature review, this study argues that communication ethics based on the principles of the Qur'an are essentially speaking correctly and honestly (sadidan), contextually (baligha), simply (maysura), gently (layyina), kindly (karima), and appropriate (ma'rufa), throughwhich one's communication is likely to be effective. In regard with the ethics of political communication, general speaking it have been regulated substantially through moral standards that have been explained in the Qur’an and the Sunnah of the Prophet Muhammad Saw. The ethics of political communication in Islam essentially reflects the broad moral and ethical principles of Islam, including the principles of honesty (al-a'dl), justice (al-qist), respect (al-ihsan), avoiding injustice (al-zulm), dialogue, tolerance (al-tasamuh), encouragement of goodness (al-amr bil ma'ruf), and constructive criticism.